'On the rocks': reproductive biology of the endemic toad Xanthophryne (Anura: Bufonidae) from the Western Ghats, India. Issue 39 (25th October 2016) - Gaitonde, Nikhil; Giri, Varad; Kunte, Krushnamegh
ABSTRACT: Xanthophryne is a toad genus endemic to the northern Western Ghats of India, with two extant sister species – Xanthophryne koynayensis and Xanthophryne tigerina . Both species are local endemics and endangered. We studied reproductive biology of these toads and found that they are specialized to the lateritic rocky outcrops at mid-elevations in high rainfall areas. Xanthophryne toads have sporadic, multiple spawning bouts lasting 2–4 days during early monsoon. In this explosive breeding behaviour, we observed male toads to engage in 'pelvic thrusts', a unique and novel behaviour among anurans. Females oviposit in shallow pools in depressions of lateritic boulders where their tadpoles metamorphose. These ephemeral rocky pools have limited resources and they desiccate rapidly with a break in the rains. To mitigate the stochastic risk of desiccation and subsequent large-scale egg/tadpole mortality, females may disperse their reproductive investment spatially and temporally in multiple clutches, and tadpoles metamorphose rapidly. Here, we describe the amplexus, spawning and male advertisement call, and provide a comparative account of the life history traits of the two Xanthophryne species. These toads face numerous threats and are in need of urgent conservation action. These toads, seemingly well adapted to the isolated rocky outcrops, offer an excellent opportunity to understand endemism, mating systems, anuran ecology and behaviour.